Curriculum as a space of opportunities: adaptations and understanding of Mathematics teachers about inclusive education - Lana Thaís Santos Silva; Veleida Anahi Cápua Silva Charlot; João Paulo Attie (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2023)
This article presents a bibliographical research, of a qualitative nature, which aimed to: a) identify the main curricular adaptations in the teaching of Mathematics to serve students from the perspective of inclusive education; b) analyze how teachers recognize themselves in the curriculum production process, respecting the specificities of students. Data collection was carried out by reading selected works that address the theme of inclusive mathematics teaching. Regarding the examination of the data, we opted for Content Analysis. As a result, we can point out that flexibility in the curriculum is fundamental within the process of school inclusion, and in the teaching of mathematics, adaptations in games, problem solving, as well as contextualization and socialization are indicators that collaborate in the learning process of students, with or without disabilities.